Implementation of the 2013 Curriculum in Mathematics Learning at the High School Level - Ananda, Mouly (EDUCTUM: Journal Research, 2023)
The curriculum is the spearhead for carrying out educational activities. Without a program, education cannot function normally effectively and efficiently as it should. The 2013 program is a replacement for the 2006 Unit Level Teaching Program (KTSP) which aims to ensure that Indonesian education can produce productive people, creative and innovative by strengthening the level of integrated attitudes, skills and knowledge. This research aims to describe the obstacles faced by teachers when implementing the 2013 mathematics curriculum at senior high school (SMA) level. This research uses a literature review method, including collecting reading sources from journals, accompanying books and relevant books. The results of the research show that the implementation of the 2013 education program, especially at the high school level, still has obstacles starting from the planning stage which includes building, developing the program and preparing lesson plans: at the implementation stage, teachers experience difficulties in adapting the lesson plans to be implemented in the classroom, where teachers still apply the same teaching methods. requires students to be more active in class and some student teachers are still not able to optimally use classroom learning aids to support interesting mathematics learning; and at the research stage, not all teachers use the standards that have been prepared in the RPP.